2012
DOI: 10.1371/journal.pone.0039801
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Transcriptomic and RNAi Analysis Identifies AIM1, ERGIC1, TMED3 and TPX2 as Potential Drug Targets in Prostate Cancer

Abstract: Prostate cancer is a heterogeneous group of diseases and there is a need for more efficient and targeted methods of treatment. In this study, the potential of gene expression data and RNA interference technique were combined to advance future personalized prostate cancer therapeutics. To distinguish the most promising in vivo prevalidated prostate cancer drug targets, a bioinformatic analysis was carried out using genome-wide gene expression data from 9873 human tissue samples. In total, 295 genes were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 58 publications
6
49
1
Order By: Relevance
“…The results show that siRNA can lower the expression of TPX2, inhibit cell proliferation, and induce apoptosis, especially 72 h after siRNA transfection. Cell cycle was blocked at S phase and cell differentiation and proliferation were also inhibited, which is consistent with results previously reported [32,33].…”
Section: Discussionsupporting
confidence: 92%
“…The results show that siRNA can lower the expression of TPX2, inhibit cell proliferation, and induce apoptosis, especially 72 h after siRNA transfection. Cell cycle was blocked at S phase and cell differentiation and proliferation were also inhibited, which is consistent with results previously reported [32,33].…”
Section: Discussionsupporting
confidence: 92%
“…Mechanistically, TPX2 exerts protumorigenic functions by promoting tumor growth and metastasis [8,10,11,12,13,14,15,16,17,18,19,20,21]. Previous studies have demonstrated that TPX2 is important in the regulation of tumor growth and is a promising diagnostic and therapeutic target for cervical cancer [10,14].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Vainio et al . demonstrated that TMED3 may be used as one of powerful targets to overcome prostate cancer . Hao et al .…”
Section: Discussionmentioning
confidence: 99%